Does Regionality Influence Students' Perceived Employability and Career Orientation? A Study of Students at an Australian University - Bennett, Dawn; Knight, Elizabeth; Koshy, Paul; Ian, Li (Society for the Provision of Education in Rural Australia (SPERA), 2021)
Insufficient access to specialised career development within many rural, regional and remote (RRR) areas contributes to persistent differences in the higher education participation rates of young people from these areas. This paper reports on research conducted with 4,993 students at a university in Western Australia who self-assessed their perceived employability (career capabilities) and career orientation. Data were analysed by year and mode of study, location, gender and discipline. Comparisons were made between RRR students and their metropolitan peers. The findings compare perceptions of employability and career orientation among RRR students in comparison with domestic metropolitan students. This shows a level of commonality between the two groups, with lessons from research on RRR students being applicable to metropolitan students.